Mainstreaming Madrasahs and Pesantrens in the East Java Province - Jahroni, Jajang (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2007)
Madrasahs and pesantrens are two Islamic educational institutions that have a very strategic role in the development of lndonesian society. Both act as sources of education for the Muslim youth ftom the middle and lower classes in the villages, not to mention a good number of upper-class children from the cities. The importance of madrasahs and pesantrens is evident when we realize that a large proportion of Indonesia's population lives in villages, and a large percentage of these are poor; thus education through madrasahs and pesantrens is often the only avenue left for those who are poor. The old order and New order regimes in the past actively pursued policies of marginalizing these education institutions and such a policy must be brought to an end. This is because the fate of the people of this country is closely tied to the success and development of Islamic educational institutions.DOI: 10.15408/sdi.v14i1.571